Application of the Induced Membrane Technique for Forearm Bone Defects: Our Institutional Experience. Issue 1 (March 2016) - Calori, Giorgio M.; Giannoudis, Peter V.; Mazzola, Simone; Colombo, Massimiliano
Abstract : The surgical treatment of forearm fracture nonunions remains a therapeutic challenge for orthopedic trauma surgeons. Nonunions of the forearm diaphysis, although not frequent, cause severe anatomic and functional impairment related to disturbance of the interosseous membrane and dysfunction of the adjacent elbow and wrist joints. Lately the induced membrane technique has been proposed for the reconstruction of large diaphyseal bone defects. In this study we present our experience of using this technique for the treatment of diaphyseal forearm bone defects with specific emphasis on the steps of the technique.